Exploring how gifts are discovered and why talents develop in sport - Trackle, P. (2005)
This thesis has attempted to advance knowledge and understanding of giftedness and talent in sport. Difficulties concerning conceptual clarity and issues concerning the origin of talent have slowed the advancement of this field of inquiry. By recognising the divisions that have occurred within the literature due to approach and presupposition, Gagne's (2000) Differentiated Model Of Giftedness and Talent was applied to reorganise the literature and establish a more sturdy conceptual base from which to launch new research. From this view, it became more appropriate to divide and describe talent as the discovery of giftedness and the development of talent. By reorganising previous research with this distinction, previous questions became inappropriate and new avenues of approach were revealed. In the past, research had questioned how talents develop and how gifts could be used to predict talent. However, it now became appropriate to consider how gifts are discovered and why talent develops. To this end, phenomenological interviews were conducted with expert coaches, gifted individuals and their families in an effort to explore how gifts were discovered and why individuals committed themselves to developing talent. This approach facilitated the reconstruction of subjective experience which was necessary to explore the multidimensional and interdependent nature of talent. The results gave a deep insight into the views and experiences of people who were, or who understood giftedness and talent. To express these findings, a new empirically based model has been proposed to explain how gifts are discovered and why talents develop.